Стихотворения и песни - Высоцкий Владимир Семенович (Поэзия XX века, 2008)
Экземпляры: ф.9 (20160226) / Инвентарный номер: 054611 / Цена: 105.05 / Авт.знак: В 93 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6